Combining Two Chaos Maps and Determining Selective Methods for MSB Bits in a Digital Image Encryption Algorithm - Munir, Rinaldi (Universitas Amikom Purwokerto, 2024)
In order to reduce the computational volume, we employ selective encryption approaches in conjunction with a chaos-based picture encryption algorithm in this research. Two chaos maps are used, namely Arnold Cat Map and Logistic Map. Before encryption, the image is scrambled with Arnold Cat Map, then selective encryption techniques are applied by selecting only four MSB bits from each pixel to be XORed with the keystream generated from the Logistic Map. Experimental results show that the use of both chaos functions can produce confusion and diffusion effects, and the use of selective encryption techniques only processes 50% of the entire image data. The encrypted image shows a relatively uniformly distributed histogram, making it difficult for attackers to perform statistical analysis to find the key or plain image. Chaos sensitivity shows that this algorithm is safe from exhaustive-key search attacks. This method is sensitive to modest changes in the key, making it safe from exhaustive-key search assaults, according to experiments conducted by gently altering the initial value of chaos. This technique is immune to brute-force attacks because of its sufficiently huge key space.